Energy-aware optimal slot allocation scheme for wearable sensors in first responder monitoring system. (5th June 2019) - Atiq, Mahin K.; Mehmood, Kashif; Niaz, Muhammad Tabish; Kim, Hyung Seok
In recent advances in first response techniques, the uniform of each first responder working in the emergency field may be equipped with sensors and a gateway. These wearable sensors in conjunction with the gateway constitute a first responder monitoring system (FRMS). FRMS gathers data about the first responders vitals and the surrounding environment, which is then transmitted to the incident commander. For the energy-constrained nature of the FRMS, an energy-efficient slot allocation scheme is proposed. The energy-efficient scheme involves the design of an optimal slot allocation scheme based on Hungarian algorithm for sensor data collection and an energy-aware sensing and transmission scheme for sensor nodes. Simulation results demonstrate the superiority of proposed scheme in terms of lifetime, residual energy, and energy-delay product as compared to greedy and first-in-first-out (FIFO) slot allocation schemes.